The Understanding of Doctors and Nurses’ Roles in Islamic Medical Practice and Rukhsah Solat in a Shariah Friendly Hospital - Mohd Arifin, Siti Roshaidai; Mohd Nazir, Nur Afiqah; Daud, Normadiah; Samsudin, Suhaiza (2021)
The medical service quality could be influenced by various factors such as medical care etiquettes, healthcare practitioners’ quality and healthcare practitioners’ advice. The implementation of Islamic healthcare services within Shariah compliant hospital faces some challenges due to lack of awareness, ethics and spirituality among healthcare practitioners. Despite these challenges, less attention has been given to the healthcare practitioners’ perspectives of their roles in delivering such services. The aim of this study was to assess the understanding of healthcare practitioners on their roles in Islamic medical practice (IMP) in a Shariah compliant hospital. This descriptive cross-sectional study was conducted among 152 nurses and doctors in a Shariah compliant hospital in Pahang, Malaysia using a set of questionnaires related to the understanding of IMP and knowledge of Rukhsah Solah. Whilst 80.3%, (n=122) participants had high level of understanding on IMP, only 50% (n=76) of them had good level of knowledge regarding Rukhsah Solah. Their departments (ward/ clinic disciplines), age, and years of experiences have significant association with the level of understanding of IMP with p-value of 0.04, 0.05 and 0.02 respectively. The department is also significantly associated with the level of knowledge regarding Rukhsah Solah (p-value < 0.00). The findings from this study suggested that more training on Rukhsah Solah should be designed for nurses and doctors working in a Shariah compliant hospital to support the implementation of IMP.